NHEC 2nd Annual Training Institute Agenda - National Hispanic Environmental Council (National Hispanic Environmental Council)
Six day program/ agenda of the NHEC 2nd Annual "CA MINORITY YOUTH ENVIRONMENTAL TRAINING INSTITUTE" that spans from Thursday, June 25 to Tuesday, June 20, 2009.